Protocol and clinical characteristics of patients under 'at-home care' for COVID-19 in South Korea: a retrospective cohort study. Issue 6 (2nd June 2022) - Park, Jin Ju; Seo, Yu Bin; Lee, Jacob; Na, Sun Hee; Choi, Young Kyun
Abstract : Objective: As the number of patients with COVID-19 increased, at-home care was introduced for the first time in South Korea. This study aimed to analyse the characteristics and outcomes of patients who were treated under at-home care. Design, setting and participants: This retrospective cohort study targeted patients under at-home care for COVID-19 in Yeongdeungpo-gu in Seoul, Korea, from 18 October 2021 to 12 December 2021. The public health centre selected eligible patients for at-home care and registered with our institution. Nurses monitored patients, and doctors decided to transfer healthcare facilities and release the quarantined patients according to their symptoms. Outcome measures: Patient characteristics during the course of at-home care. Results: A total of 1422 patients were enrolled and 9574 patient-days were managed. Most patients were aged ≥60 years (22.7% (n=323)), and 82.8% did not have underlying conditions. The median length of care for patients was 8 days (IQR: 5–10 days). During the study period, 986 (69.3%) patients were released from quarantine, 82 (5.8%) patients were transferred to facilities and 354 (24.9%) patients were still under at-home care at the end of the study period. The most common cause of transfer was sustained fever (n=30; 36.6%), followed by dyspnoea and desaturation (n=17; 20.7%). Factors associated with transfer were diabetes (OR: 3.591, 95% CI 1.488 to 8.665, p=0.004), pregnancy (OR: 5.839, 95% CI 1.035 to 32.935, p=0.046) and being presymptomatic at diagnosis (OR: 4.015, 95% CI 1.559 to 10.337, p=0.004). Conclusions: There were no specific problems related to patient safety when operating at-home care. Patients with risk factors, such as diabetes, were more likely to be transferred to healthcare facilities. For safe at-home care, it is necessary to prepare for an appropriate response to the emergency.